Flow-Mediated Vasodilatation which is diagnostic method of endothelial dysfunctions change in atrial septal defect patients before and after closure of the ASD (Annals of Medical Research, 2021)
Aim: Atrial septal defect secondary pulmonary hypertension causes disruption of the endothelial structure, resulting in an increase in vasoconstrictor mediators and a decrease in vasodilator mediators. These changes on the endothelial system alter the flow in the pulmonary vein and the systemic vein bed. This also has an effect on flow mediated vasodilatation. Our purpose in this study is to evaluate the endothelial dysfunction after atrial septal defect closure via flow mediated vasodilatation. Material and Methods: Total 51 patients with pre and one mount after post treatment secundum-type atrial septal defect and 40 healthy volunteers were prospectively enrolled. Atrial septal defect was treated with transcathater closure procedure. Flow mediated vasodilatation was measured to evaluate endothelial function prior to and one month after the defect was closured.Results: Flow-mediated vasodilatation values were significantly higher in an atrial septal defect′s patient than in the healthy volunteer (11.2 ± 1.01 m/s vs. 12.7 ± 1.18 m/s, P 0.001). Flow-mediated vasodilatation values were significantly reduced at the follow-up one month after the procedure compared to baseline. Moreover, there was a significant negative correlation between pulmonary arterial pressure values and flow-mediated vasodilatation (r=-0.347; p=0.013) in the pretreatment group.Conclusion: Flow-mediated vasodilatation values were significantly lower in the right cardiac chambers, and the systolic pulmonary arterial pressure was improved. This result has shown us that atrial septal defect closure may benefit from endothelial dysfunction.
Keywords: Atrial septal defect; endothelial dysfunction; flow-mediated vasodilatation